POSHAN's abstract digest on maternal and child nutrition research - Issue 36 - Avula, Rasmi (International Food Policy Research Institute, 2020)
As India continues its dual battle – one against coronavirus pandemic and the second against malnutrition, this issue of Abstract Digest brings to you a collection of articles that are primarily India-focused and a few of them discuss measurement of outcomes and implications. Given below is the list of peer-reviewed articles in this issue on the outcomes, determinants and interventions pertaining to maternal and child nutrition. Please click on the title if you wish to go straight to the article or scroll down to explore the abstract in the pages that follow.